Pembelajaran MBKM dengan Capaian Akhir Sistem E-commerce Platform (Benchmark OLX) di Binar Academy - Ade Safarudin Madani; Giri Wahyu Wiriasto; Misbahuddin (Jurnal Pengabdian Magister Pendidikan IPA, 2022)
The MBKM Program is one of the policies of the Minister of Education and Culture regarding students being able to take studies outside the campus which aims to improve competence according to the needs of the times. Through the Independent Study MBKM activity at Binar Academy, this is one of the implementations in achieving the Ministry of Education and Culture's program in forming students who are able to compete socially, cooperate, self-management and work demands at a time of rapid development. The project case was carried out at PT. Lentera Terang Benderang or Binar Academy as a partner, a technology company that facilitates MBKM learning with the bootcamp method. Bootcamp lasted for approximately 5 months carried out with several stages and the learning process was carried out synchronously and asynchronously. The final bootcamp activity is carried out by making a final project in the form of an E-commerce application system with OLX benchmarks that can be used as buying and selling used goods. Final project work with Agile Model, especially Scrum because it is able to design scalable applications in a relatively short time. The final project of the system development was successfully developed as an e-commerce system for an online buying and selling site specifically for selling used goods.